Efficient adsorption performance of an alginate-based dental material for uranium(vi) removal - Erden Kadriye Esen (Open Chemistry)
The study aimed to explore the potential of Kromalgin, a cost-effective and readily available dental material, as a sustainable solution for the removal of U(VI) metal ions from aqueous solutions. In this context, Kromalgin, a single-use dental impression material discarded after each application, was employed for uranium adsorption, addressing the environmental concern of radioactive pollution while simultaneously providing a method for recycling dental waste. The parameters affecting the adsorption of U(VI) ions on the adsorbent, such as pH, amount of adsorbent, concentration of uranium ions, temperature, and contact time, were examined. Under optimum conditions, a 94.56% adsorption efficiency was achieved. The experimental results of adsorption of U(VI) ions on Kromalgin were evaluated by applying the Langmuir, Freundlich, and Dubinin–Radushkevich isotherm models. According to the obtained data, the adsorption of U(VI) ions on Kromalgin complies with all three isotherm models. Thermodynamic parameters such as enthalpy change (ΔH 0), free energy change (ΔG 0), and entropy change (ΔS 0) were calculated, indicating that the adsorption process is spontaneous and endothermic in nature. The results indicate an adsorption capacity of 142.86 mg g−1 and an adsorption energy of 17.81 kJ mol−1. The abundance, cost-effectiveness, and highly effective results of Kromalgin have positioned it as a reasonable option for U(VI) removal.